Effect of High Dose Active Vitamin D Therapy on the Development of Hypocalcemia After Subtotal Parathyroidectomy in Patients on Chronic Dialysis - Grube M (Dove Medical Press, 2021)
Malina Grube,1 Frank Weber,2 Anna Lena Kahl,3 Andreas Kribben,1 Nils Mülling,1 Walter Reinhardt1 1Department of Nephrology, University Hospital Essen, Essen, Germany; 2Department of General-, Visceral- and Transplantation Surgery, Section of Endocrine Surgery, University Hospital Essen, Essen, Germany; 3Institute of Medical Psychology and Behavioral Immunobiology, University Hospital Essen, Essen, GermanyCorrespondence: Nils MüllingDepartment of Nephrology, University Hospital Essen, Hufelandstr. 55, Essen, 45147, GermanyEmail nils.muelling@uk-essen.deBackground: The period after parathyroidectomy (PTx) in dialysis patients is characterized by periods of severe hypocalcemia. This study aims to investigate the effect of high doses of active vitamin D immediately after PTx on the development of hypocalcemia.Materials and Methods: We retrospectively reviewed 111 patients with secondary hyperparathyroidism receiving subtotal PTx between 2010 and 2019. A high dose group “HDG” (n = 67) receiving 12 μg alfacalcidol in combination with 8.550 mg calcium acetate per day, which was then adapted according to lab values, was compared with a low dose group “LDG” (n = 44) receiving up to 4 μg alfacalcidol per day. The laboratory values were recorded up to ten weeks postoperatively.Results: The assumed drops in parathyroid hormone (PTH) and calcium were observed in both groups after PTx. We observed significantly lower calcium values in the LDG between days 4 and 18 postoperatively than in the HDG (p < 0.001). The proportion of severe hypocalcemia after PTx (total calcium < 1.5 mmol/l) in the HDG was 8.5% on day 1 and 47% on day 4 in the LDG. Intravenous calcium requirements were significantly lower in the HDG (7.6%) than in the LDG (45.7%; p = 0.001).Conclusion: The period after PTx in dialysis patients is characterized by an expected drop in PTH and calcium within the first days. Ongoing high turnover is observed in the 2nd and 3rd week after PTx. Administering high doses of alfacalcidol combined with calcium acetate diminishes the episodes of severe hypocalcemia and the need for intravenous calcium.Keywords: secondary hyperparathyroidism, hungry bone disease, parathyroidectomy, vitamin D, dialysis, CKD stage 5